Cybersecurity and human rights in the age of cyberveillance - Kulesza, Joanna; Balleste, Roy (Lanham : Rowman & Littlefield, 2016)
"Cybersecurity and Human Rights in the Age of Cyberveillance is a collection of articles by distinguished authors from the U.S. and Europe and presents a contemporary perspective on the limits online of human rights. By considering the latest political events and case law, including the NSA PRISM surveillance program controversy, the planned EU data protection amendments, and the latest European Court of Human Rights jurisprudence, it provides an analysis of the ongoing legal discourse on global cyberveillance. Using examples from contemporary state practice, including content filtering and Internet shutdowns during the Arab Spring as well as the PRISM controversy, the authors identify limits of state and third party interference with individual human rights of Internet users. Analysis is based on existing human rights standards, as enshrined within international law including the Universal Declaration of Human Rights, International Covenant on Civil and Political Rights, European Convention on Human Rights and recommendations from the Human Rights Council. The definition of human rights, perceived as freedoms and liberties guaranteed to every human being by international legal consensus is presented based on the rich body of international law."--Publisher description.
Defining cybersecurity : critical infrastructure and public-private partnerships / Joanna Kulesza -- Cybersecurity and state responsibility : identifying a due diligence standard for prevention of transboundary threats / Dimitrios Delibasis -- In harm's way : harmonizing security and human rights in the internet age / Roy Balleste -- Privacy versus security : identifying the challenges in a global information society / Rolf H. Weber and Dominic N. Staiger -- Freedom of expression, human rights standards, and private online censorship / Monica Horten -- (Global) internet governance and its discontents / M.I. Franklin -- Walled gardens or a global network? : tensions, (de-)centralizations and pluralities of the internet model / Francesca Musiani -- National security and U.S. constitutional rights : the road to Snowden / Richard B. Andres -- Attribution policy in cyberwar / Kalliopi Chainoglou.
Includes bibliographical references (pages 189-213) and index.
Keywords: Computer networks -- Security measures; Computer security; Human rights; Cyberspace -- Social aspects; Computer networks -- Security measures; Computer security; Cyberspace -- Social aspects; Human rights